Mauritania - Improving the Management of Public Resources : Innovative Approaches - World Bank (Washington, DC, 2012)
A common image of Mauritania is one of a sparsely populated country, with a nomadic population, limited physical resources and poor social and economic indicators. This was indeed the case only a decade ago. Less well-known is the fact that since about 1992 Mauritania has successfully managed a major transition to economic and political liberalization and has, with the support of the World Bank and the International Monetary Fund (IMF), implemented a far-reaching set of macro-economic and structural reforms. Results obtained so far are considerable: public finances have been stabilized, private sector investment is growing, social indicators are improving, and poverty is declining. There are also negative effects, including heavy rural-urban migration, high urban unemployment and growing demands for social services and infrastructure. Clearly, while the transition to a market-oriented economy has begun, the process is not complete. To maintain the momentum of the economic reforms begun in 1992 and to consolidate the gains made so far, the government decided in 1994/95 to improve the mobilization, allocation and management of its public resources. It developed a Public Resource Management Program which had the following objectives: 1) strengthen economic policy-making capacity; 2) improve domestic resource mobilization by broadening and diversifying the tax base; 3) improve public expenditure allocation and management; and 4) modernize public administration to better meet the needs of a market-oriented economy.